2009
DOI: 10.1111/j.1949-8594.2009.tb17872.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Middle School Girls’ Science Identities: Examining Attitudes and Perceptions of Scientists when Working “Side‐by‐Side” with Scientists

Abstract: This article is the culmination of an extensive inquiry‐focused interactive experience involving female middle school students and five university scientists, which demonstrated that middle school girls ‘perception of science and scientists can be successfully improved. The study exposed students to adult professional scientists over a period of a few days in laboratory and field exercises. Based on student journal entries and pictorial illustrations, as well as attitude surveys, the experience resulted in a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…By examining in detail how peers socially interact during a science camp, our study both supports and extends previous studies on identity outcomes that result from science camp programs (Bhattacharyya et al, 2011;Farland-Smith, 2009;Frost & Wiest, 2007;Wheaton & Ash, 2008). Prior research studies in this area have pointed to specific identity-related outcomes for youth participating in science camp programs such as attitudes toward science (Bhattacharyya et al, 2011;Farland-Smith, 2009), career aspirations (Bhattacharyya et al, 2011;Farland-Smith, 2012), confidence (Frost & Wiest, 2007), and views of science and scientists (FarlandSmith, 2009;Wheaton & Ash, 2008). While our study also highlighted identity-related outcomes of a science camp program, it adds essential insight into a possible mechanism of identity development.…”
Section: Conclusion and Theoretical Implicationssupporting
confidence: 82%
See 1 more Smart Citation
“…By examining in detail how peers socially interact during a science camp, our study both supports and extends previous studies on identity outcomes that result from science camp programs (Bhattacharyya et al, 2011;Farland-Smith, 2009;Frost & Wiest, 2007;Wheaton & Ash, 2008). Prior research studies in this area have pointed to specific identity-related outcomes for youth participating in science camp programs such as attitudes toward science (Bhattacharyya et al, 2011;Farland-Smith, 2009), career aspirations (Bhattacharyya et al, 2011;Farland-Smith, 2012), confidence (Frost & Wiest, 2007), and views of science and scientists (FarlandSmith, 2009;Wheaton & Ash, 2008). While our study also highlighted identity-related outcomes of a science camp program, it adds essential insight into a possible mechanism of identity development.…”
Section: Conclusion and Theoretical Implicationssupporting
confidence: 82%
“…Findings across these studies reviewed suggested that identity-related outcomes clustered in the following ways: views of science (Farland-Smith, 2012; Gonsalves et al, 2013;Wheaton & Ash, 2008), attitudes toward science (Bhattacharyya, Mead, & Nathaniel, 2011;Farland-Smith, 2009), confidence (Frost & Wiest, 2007), and career choices (Bhattacharyya et al, 2011;Tan et al, 2013). For example, participation in out-of-school science programs broadened youth's definition of what counted as science (Gonsalves et al, 2013;Wheaton & Ash, 2008).…”
Section: Out-of-school Science Learningmentioning
confidence: 94%
“…Finally, 10 articles reported studies that were interested in I/M/A in the context of S&T summer camps. These were intensive activities, sometimes away from home, of sometimes considerable duration (six weeks), with specific and explicit agendas and objectives (developing scientific career aptitudes [187], girls' interest in S&T careers [64], using LEGO sets [145]). Most of the research used only post-tests, while others established comparisons with pretests [205] or with data obtained from other research on equivalent students and where no special intervention was made [148].…”
Section: Summer Camps/competitions/science Fairs/field Tripsmentioning
confidence: 99%
“…Engineering experiences can bring a real-world engagement for students towards understanding mathematical functions (Sharp, Zachary, & Luttenegger, 2006) and scientific concepts (Youl, 2001). Although some studies have investigated how STEM education may be embedded within science classes (Cantrell, Pekcan, Itani, & Velasquez-Bryant, 2006), most existing studies appear to investigate STEM within secondary schools (e.g., Donna, 2009). In addition, pedagogical knowledge for STEM education appears in need of further study to better inform the teaching of STEM disciplines.…”
Section: Introductionmentioning
confidence: 99%